Numerical Investigation on the Performance of Cyclone Separators - Tran, Thanh Tinh; Nguyen, Dang Khoa (Journal of Technical Education Science, 2023)
Cyclone separators are commonly employed in the solid particle separation process due to their simplicity and low-cost manufacture. Collection efficiency and pressure drop are two of the most important factors. Small-size cyclone separator has outperformed collection efficiency. However, due to its small size, it’s hard to detailed flow investigation experimentally. So, the target of this work is to perform a numerical investigation of the flow characteristics as well as the collection efficiency and pressure drop of small cyclone separators, using Ansys Fluent software. Discrete Phase Model is included to simulate the particle-flow interaction. Different values of velocity inlet and particle size are considered. Typical flow characteristics of cyclone separators with a strong vortex are revealed. Results also show that the larger particle size or the stronger inlet velocity provides higher collection efficiency. Particularly, for a typical particle diameter of 2.96 micrometers, the collection efficiency of the cyclone separator is always higher than 91% when the inlet velocity surpasses 15 m/s. All these results provide a valuable framework for the operation of cyclone separators.